Crustal Thermal Structure and Exhumation Rates in the Southern Alps Near the Central Alpine Fault, New Zealand. (4th August 2020) - Michailos, Konstantinos; Sutherland, Rupert; Townend, John; Savage, Martha K.
Abstract: We investigate orogenic uplift rates and the thermal structure of the crust in the hanging wall of the Alpine Fault, New Zealand, using the hypocenters of 7, 719 earthquakes that occurred in the central Southern Alps between late 2008 and early 2017, and previously published thermochronological data. We assume that the base of the seismogenic zone corresponds to a brittle‐ductile transition at some fixed temperature, which we estimate by fitting the combined thermochronological data and distribution of seismicity using a multi‐1‐D approach. We find that exhumation rates vary from 1 to 8 mm/yr, with maximum values observed in the area of highest topography near Aoraki/Mount Cook, a finding consistent with previous geologic and geodetic analyses. We estimate the temperature of the brittle‐ductile transition beneath the Southern Alps to be 410–430°C, which is higher than expected for Alpine Fault rocks whose bulk lithology is likely dominated by quartz. The high estimated temperatures at the base of the seismogenic zone likely reflect the unmodeled effects of high fluid pressures or strain rates. Plain Language Summary: The Southern Alps of New Zealand have formed during the last 10 million years as a result of collision between the Pacific and Australian plates. The Alps are bounded to the northwest by the Alpine Fault, which produces earthquakes of magnitude ∼8 every 300 years. Using observations of 7, 700 much smaller earthquakes that occurred between 2008 and 2017, and 150 thermochronological measurements, which give the times at which different minerals cooled below specific temperatures, we have constructed a thermal model of the Southern Alps that enables us to estimate the rates at which the Alps are being uplifted and hence to estimate the temperature at the source locations of earthquakes. The pattern of uplift we determine is consistent with previous geological and geodetic results and enables us to calculate the temperature at which each earthquake occurred. The base of earthquake activity is at 410–430°C, which is hotter than anticipated. We suggest that high fluid pressures or strain rates cause the Southern Alps to deform at higher temperatures than would otherwise be the case. The shallowing of seismicity near Aoraki/Mount Cook, where we estimate rapid uplift and erosion at 8±3 mm/yr, is conspicuous, though we also estimate high temperatures for earthquakes elsewhere in the Southern Alps, where uplift rates are inferred to be 1–2 mm/yr. Key Points: We use seismic and thermochronological data to determine the thermal structure of the crust in the central Southern Alps Exhumation rates of 8±3 mm/yr are localized near Aoraki/Mount Cook, with peak exhumation rates elsewhere of 1–2 mm/yr High modeled BDT zone temperatures of 410–430°C may reflect the effects of elevated fluid pressures and/or high strain rates